2009
DOI: 10.3109/09638280903177243
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of cognitive behavioural factors as predictors of pain, disability and quality of life one year after lumbar disc surgery

Abstract: Eliciting patients' expectations on work return after surgery could contribute to early identification of those who run the risk of developing long-term disability and sick-leave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 52 publications
5
65
0
1
Order By: Relevance
“…Johansson et al [17] , among others, found that cognitive behavioral factors predict pain, disability and quality of life after surgery. The results of this study reveal an association between spine surgical patients' and their family members' coping resources and their overall coping (see Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Johansson et al [17] , among others, found that cognitive behavioral factors predict pain, disability and quality of life after surgery. The results of this study reveal an association between spine surgical patients' and their family members' coping resources and their overall coping (see Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been confirmed that patients' expectations on work return have an influence on pain, sick leave and disability and that their fear-avoidance beliefs contribute to a low quality of life [17] . Patients' higher levels of optimism and expectations have been found to result in better perceived quality of life and in work return within a year following surgery [17,30] . An association has been demonstrated between active coping and physical recovery from surgery [31] .…”
Section: Purpose and Theoretical Background Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A significant proportion of patients, however, suffer from ongoing or recurrent low back pain years after surgery, despite an obviously successful operation (Valen et al 1998;Krämer 2006). During the past two decades, several physiological and psychosocial predictors of ongoing/recurrent complaints after surgery have been identified (Schade et al 1999;Boer et al 2006;Edwards et al 2007;Peters et al 2007;Johansson et al 2010), and biopsychosocial approaches explore their complex relationships (Melzack 2005;Geiss et al 2005;Gatchel et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Third, the use of only control over pain was not adequate to assess pain-related thoughts. It has been discussed that hope for relief from pain, 23 self-efficacy, 24 and a sense of coherence 25 are cognitive factors associated with pain.…”
Section: Study Limitationsmentioning
confidence: 99%